2008
DOI: 10.1111/j.1600-0765.2008.01051.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential gender effects of a reduced‐calorie diet on systemic inflammatory and immune parameters in nonhuman primates

Abstract: Dietary manipulation, including caloric restriction, has been shown to significantly impact host response capabilities, particularly associated with aging. This investigation compared systemic inflammatory and immune response molecules in rhesus monkeys (Macaca mulatta) on continuous long term calorie-restricted (CR) diets with a matched group of animals on a control diet, examining the effects of both gender and aging. The results demonstrated that haptoglobin and α 1 antiglycoprotein were elevated in serum o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 89 publications
3
53
1
Order By: Relevance
“…It is clear that the primate model has provided the essential bridge for understanding the interaction of selected members of the subgingival microbiota with the host, particularly as reflected by the longitudinal alterations, which occur in the clinical and microbiological progression of ligature-induced periodontitis similar to the human periodontal experience (Madden and Caton, 1994, Persson et al, 1993). We and others have shown that characteristics of the inflammatory response and systemic humoral immune responses that accompany ligature-induced periodontitis in nonhuman primates parallel those observed in human periodontitis (Ebersole et al, 2010, Ebersole et al, 2009, Ebersole et al, 2008b, Ebersole et al, 2002, Persson et al, 1994). Soluble receptors to IL-1 and TNF significantly inhibited recruitment of inflammatory cells in close proximity to bone, reduced osteoclast formation, and reduced bone loss in ligature-induced periodontitis in a nonhuman primate animal model (Assuma et al, 1998, Delima et al, 2001).…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…It is clear that the primate model has provided the essential bridge for understanding the interaction of selected members of the subgingival microbiota with the host, particularly as reflected by the longitudinal alterations, which occur in the clinical and microbiological progression of ligature-induced periodontitis similar to the human periodontal experience (Madden and Caton, 1994, Persson et al, 1993). We and others have shown that characteristics of the inflammatory response and systemic humoral immune responses that accompany ligature-induced periodontitis in nonhuman primates parallel those observed in human periodontitis (Ebersole et al, 2010, Ebersole et al, 2009, Ebersole et al, 2008b, Ebersole et al, 2002, Persson et al, 1994). Soluble receptors to IL-1 and TNF significantly inhibited recruitment of inflammatory cells in close proximity to bone, reduced osteoclast formation, and reduced bone loss in ligature-induced periodontitis in a nonhuman primate animal model (Assuma et al, 1998, Delima et al, 2001).…”
Section: Introductionmentioning
confidence: 53%
“…The accepted paradigm from these observations is that the disease in aging represents an accumulation of noxious challenge over time linked with more general disruptions in the integrity of the periodontal tissues (Hajishengallis, 2010, Gonzalez et al, 2011, Ebersole et al, 2008b, Ebersole et al, 2008a). However, substantial literature from other models of infection has demonstrated significant age-associated increases in susceptibility to infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed decrease in serum IgG with CR evidences the effect of this regimen on the systemic humoral as well as intestinal immune responses. On the contrary, in another study with CR an increase was observed in the number of IgM and IgG cells in spleen and serum immunoglobulins (IgG and IgM) in mice and monkeys [31][32][33] These apparently contrary results could be due to the different type of dietary protocols employed. Whereas Ebersole et al [31] used an energy-restricted high fat diet or a continuous long-term calorierestricted diet, we used an alternate day calorie restriction diet.…”
Section: Discussionmentioning
confidence: 90%
“…We have also characterized the effects of aging on naturally occurring periodontitis, and we use a specific ligature-induced model of specific challenge to the oral cavity to describe acute responses of mucosal tissues during aging. In addition, this model has allowed us to document gender and diet effects on local and systemic inflammatory and immune responses that are altered with aging (25). FIG.…”
Section: Fig 5 Serummentioning
confidence: 99%